2011
DOI: 10.1136/bjophthalmol-2011-300934
|View full text |Cite
|
Sign up to set email alerts
|

The influence of cervical and thoracic lymphadenectomy on corneal allograft rejection in inbred rats: Table 1

Abstract: ., 2012. The influence of cervical and thoracic lymphadenectomy on corneal allograft rejection in inbred rats. British Journal of Ophthalmology, 96(3), 448-450. DOI: doi:10.1136448-450. DOI: doi:10. /bjophthalmol-2011 ©BMJ Group 2012. Please note that any alterations made during the publishing process may not appear in this version. Results All allografts underwent rejection. The median time to rejection for unmodified allografts was day 15, compared with day 14.5 for minimally lymphadenectomised recipien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…In the mouse, bilateral removal of the cervical lymph nodes induces indefinite corneal graft survival across a weak histocompatibility barrier 20. However, we have reported that the bilateral removal of some or all of the superficial cervical, facial, internal jugular and posterior cervical lymph nodes prior to corneal transplantation has no effect on the tempo or incidence of immunological rejection in the inbred WF/F344 combination 21. T cell sensitisation may occur within the eye, its environs, in other lymph nodes or the spleen.…”
Section: Discussionmentioning
confidence: 84%
“…In the mouse, bilateral removal of the cervical lymph nodes induces indefinite corneal graft survival across a weak histocompatibility barrier 20. However, we have reported that the bilateral removal of some or all of the superficial cervical, facial, internal jugular and posterior cervical lymph nodes prior to corneal transplantation has no effect on the tempo or incidence of immunological rejection in the inbred WF/F344 combination 21. T cell sensitisation may occur within the eye, its environs, in other lymph nodes or the spleen.…”
Section: Discussionmentioning
confidence: 84%
“…Nonetheless, these steps typically occur centrally, and local transgene products may be inadequate. A recent study designed to investigate the effects of cervical and thoracic lymphadenectomy on corneal graft rejection in inbred rats failed to demonstrate any difference 21. The authors suggest that sensitization and clonal expansion of corneal alloantigen-reactive cells may not be limited only to the regional lymph nodes (superficial cervical, facial, internal jugular, and posterior cervical) in rat.…”
Section: Immunology Of Corneal Graft Rejectionmentioning
confidence: 94%
“…In this issue of the BJO , Brice et al 19 have considered the intervention of regional lymph node extirpation to modulate the immune response by eliminating the site of antigen presentation and clonal expansion of effector lymphocytes. Despite the volume of effort directed towards modulating the immune system, the most significant impact on reducing the incidence of corneal graft rejection has come from an unexpected source: the surgical innovation of lamellar corneal graft surgery.…”
mentioning
confidence: 99%